Serum levels of ferritin and transferrin serve as prognostic factors for mortality and survival in patients with end‐stage liver disease: A propensity score‐matched cohort study. Issue 3 (1st April 2020) - Meier, Jörn Arne; Bokemeyer, Arne; Cordes, Friederike; Fuhrmann, Valentin; Schmidt, Hartmut; Hüsing‐Kabar, Anna; Kabar, Iyad
Abstract : Background: Patients with end‐stage liver disease are known to suffer from a significantly high risk of mortality, but accurate prediction of the course of disease is challenging. Objective: The study aim was to evaluate the independent prognostic and clinical importance of serum levels of ferritin and transferrin for 90‐day survival of patients with liver disease. Methods: Patients with end‐stage liver disease treated during a 2‐year period were enrolled retrospectively in a single‐centre study. Unmatched and propensity score matching (PSM) analyses were applied. Results: The study cohort comprised 286 patients with end‐stage liver disease, of which 22.9% died during the observational period. High serum ferritin levels and low serum transferrin levels were associated significantly with increased 90‐day mortality in the unmatched ( p < 0.001) and PSM study population ( p = 0.017). Serum levels of ferritin and transferrin had high prognostic capability to predict 90‐day survival similar to the Model for End‐stage Liver Disease. Patients with serum ferritin values >1030.5 µg/l had a 50% risk of dying within 11 days after measurement, which translated up to a 90‐day mortality of 83%. Conclusion: Serum levels of ferritin and transferrin have independent and excellent capabilities to determine prognosis in patients with end‐stage liver disease. Ferritin measurements can reliably identify those with high mortality in daily practice.